2022
DOI: 10.3390/molecules27196156
|View full text |Cite
|
Sign up to set email alerts
|

β-Caryophyllene: A Therapeutic Alternative for Intestinal Barrier Dysfunction Caused by Obesity

Abstract: Obesity is an excessive accumulation of fat that exacerbates the metabolic and inflammatory processes. Studies associate these processes with conditions and dysregulation in the intestinal tract, increased concentrations of lipopolysaccharides (LPSs) in the blood, differences in the abundance of intestinal microbiota, and the production of secondary metabolites such as short-chain fatty acids. β-Caryophyllene (BCP) is a natural sesquiterpene with anti-inflammatory properties and with the potential purpose of f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 48 publications
0
2
0
Order By: Relevance
“…Cannabinoids such as β-caryophyllene and caryophyllene oxide produce several effects on the gastrointestinal tract, which include regulating food intake, altering visceral sensation, reducing inflammation, and adjusting intestinal permeability. This permeability is mainly associated with mucus secretion and proteins that form tight junctions, with studies showing changes in mucus layer thickness and claudin-1 protein expression in the colon [ 30 ].…”
Section: Resultsmentioning
confidence: 99%
“…Cannabinoids such as β-caryophyllene and caryophyllene oxide produce several effects on the gastrointestinal tract, which include regulating food intake, altering visceral sensation, reducing inflammation, and adjusting intestinal permeability. This permeability is mainly associated with mucus secretion and proteins that form tight junctions, with studies showing changes in mucus layer thickness and claudin-1 protein expression in the colon [ 30 ].…”
Section: Resultsmentioning
confidence: 99%
“…In addition, previous studies have shown that leptin, which is highly expressed in the placenta, is involved in the development of GDM (Sweeting et al 2022 ). There is evidence that gut microbiota dysbiosis is associated with leptin expression under inflammatory conditions, but the exact interactions remain understood (Rodriguez-Mejia et al 2022 ).…”
Section: Introductionmentioning
confidence: 99%